Optimalisasi Penerapan Program Penguatan Profil Pelajar Pancasila (P5) dan Profil Pelajar Rahmatan Lil Alamin (PPRA) Melalui Pengembangan Literasi Menulis - Kurniyatul Faizah; Zidniyati Zidniyati; Luluk Maktumah (LP2M Universitas Ibrahimy, 2024)
Writing literacy is one of the programs developed at MI Tarbiyatus Shibyan grade 6 to provide writing skills for students as one of the final assignment products before graduating from Madrasah. Writing literacy is not only a technical skill, but also as a means of strengthening the values ​​of character, spirituality and social awareness promoted by the Program for Strengthening the Pancasila Student Profile (P5) and the Rahmatan Lil Alamin Student Profile (PPRA). The aim of this research is to explore the optimization of the implementation of the Pancasila Student Profile Strengthening Program (P5) and the Rahmanan lil Alamin Student Profile (PPRA). This research uses a qualitative approach with a qualitative descriptive type. Source selection uses purposive and data collection techniques using observation, interviews and documentation. The data analysis techniques used are data condensation, data presentation, and drawing conclusions. Data validation uses triangulation of sources and techniques. The results of this research are that there were 11 groups, each of which produced 11 paper talk products, which in the process integrated the P5 values, namely Mutual Cooperation, Independence and Critical Reasoning, while the PPRA values ​​applied were Deliberation (Shura), Tolerance (Tasamuh), Dynamic and Innovative (tatawur and Ibtikar).